Unilateral Agenesis of Lung, Kidney with Cardiac and Vertebral Defects a Rare Association - Maji, B; Ganguly, N; Ghosh, A (Journal of Nepal Paediatric Society, 2014)
Unilateral lung agenesis initially misdiagnosed as unilateral massive pleural effusion with collapse of lung, and after several investigations, including ultrasonography or CT scan of thorax, fibre-optic bronchoscopy or bronchography, a final diagnosis of unilateral absence of lung is made. An anomaly scan may also reveal associated renal, cardiac and vertebral defects. Here we report a 7 months old female who presented with respiratory distress since birth and after a thorough investigation, she was found to have this rare association of pulmonary-renal-cardiacvertebral defect. DOI: http://dx.doi.org/10.3126/jnps.v34i1.8898 J Nepal Paediatr Soc 2014;34(1):77-79